Open & distance learning (ODL): factors that affect mathematics results from undergraduate students’ perspective / Sumarni Abu Bakar, Faiqah Nabihah Kamsin and Mohd Rijal Ilias - Abu Bakar, Sumarni; Kamsin, Faiqah Nabihah; Ilias, Mohd Rijal (Penerbit UiTM (UiTM Press), 2025)
Open and Distance Learning (ODL) is a learning mode in which learners and educators are separated by time and location. The new norm of the educational system that is being implemented provides students with significant opportunities to learn without boundaries. Nonetheless, the deployment of online and remote learning by higher education institutions has highlighted difficulties relating to academic achievement among students. Students enrolled with ODL have been reported to confront many individual, institutional, and instructional challenges. Therefore, this study investigated the factors that affect Mathematics results during ODL. This study used a quantitative approach and distributed online surveys to collect data from the respondents. Students from the Faculty of Education majoring in Mathematics were chosen as the population while only students who took Calculus 3 were chosen as the sample of the study. Frequency analysis and descriptive statistics were used to summarise and describe the demographic data. Besides, correlation analysis was used to determine the relationship between students’ self-regulated learning, teachers’ teaching practices, and learning facilities toward Mathematics results. In addition, regression analysis was used to determine which factors affect Mathematics results the most. The findings showed that there is a significant relationship between students’ self-regulated learning, teachers’ teaching practices, and learning facilities toward Mathematics results. Furthermore, the results revealed that self-regulated learning is the factor that affects Mathematics results the most during Open and Distance Learning (ODL). Generally, the study presented that the major factor that affects students’ academic achievement is their self-regulation followed by teachers’ teaching style and learning facilities. Therefore, students, teachers, and educational institutions may utilize the findings of this study to improve students’ academic performances in the future.